2020
DOI: 10.19052/mv.vol1.iss40.5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Brucellosis in Dogs in Enugu and Anambra States, Nigeria

Abstract: Seroprevalence of the antibodies of Brucella canis and Brucella abortus in dogs was assessed using a cross-sectional survey in Anambra and Enugu States, Nigeria. A total of 123 Companion dogs made up of 65 clinic dogs, 34 slaughter dogs and 24 household dogs were screened. For B. abortus antibody assay, the collected serum was used for Rose Bengal plate test (RBPT), Serum agglutination test (SAT) and Solid Phase Immunoassay technique with Immunocomb® Canine Brucellosis Antibody Test Kit was used. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
3
1
Order By: Relevance
“…The fact that NMBM had the highest average age of dogs (43.4 months), as compared to 29.9 months in the CJM-Gauteng and 40.6 months in the T&O, explains why NMBM had a higher risk of B. canis infection compared to the other two study areas. These findings affirm previous work of other researchers who concluded that the age of the dog, especially in sexually active dogs above 3 years of age, presents a greater risk for B. canis infection (Ayoola et al 2016; Anyaoha 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that NMBM had the highest average age of dogs (43.4 months), as compared to 29.9 months in the CJM-Gauteng and 40.6 months in the T&O, explains why NMBM had a higher risk of B. canis infection compared to the other two study areas. These findings affirm previous work of other researchers who concluded that the age of the dog, especially in sexually active dogs above 3 years of age, presents a greater risk for B. canis infection (Ayoola et al 2016; Anyaoha 2015).…”
Section: Discussionsupporting
confidence: 91%
“…All dogs up to 6 months of age were found to be seronegative because they were not sexually mature and active yet. Anyaoha (2015) revealed that in an earlier study in Nigeria, a seroprevalence of 3.4% in dogs younger than 1 year was reported, while a seroprevalence of 10.1% was reported in dogs 1–3 years old and 15.7% was reported in dogs above 3 years of age.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of the study is also higher than 21.5% reported by Osinubi et al [27] in Zaria, 5.46% by Cadmus et al [6] in South western Nigeria, zero percent prevalence reported by Anyaoha [2] in Enugu and Anambra States using RBPT, as well as 1.06%…”
Section: Discussioncontrasting
confidence: 52%
“…Location-based sero-prevalence of Brucella antibodies in dogs revealed a highest prevalence rate of 26% in Kalmai ward as compared to other wards, this may be as a result of the location of the dog market and dog slaughter slab as well as the activities of dog meat processors and dog retailers in the ward. The lowest prevalence rate (4.17%) was recorded in Bare ward, this may be as a result of less contact rate between dogs and other livestock species in the study area as observed by Anyaoha et al [2] in Enugu and Anambra…”
Section: Discussionmentioning
confidence: 58%
“…The disease is well controlled in most developed countries [11], but common in Africa, South America, Asia, the Caribbean, Middle East and the Mediterranean basin [12,2,13]. In livestock production, the major economic effects are due to abortion, premature birth, reduced milk production, repeat breeding and cost of veterinary care [14].…”
Section: Introductionmentioning
confidence: 99%